2015
DOI: 10.1159/000368806
|View full text |Cite
|
Sign up to set email alerts
|

LRAT Overexpression Diminishes Intracellular Levels of Biologically Active Retinoids and Reduces Retinoid Antitumor Efficacy in the Murine Melanoma B16F10 Cell Line

Abstract: Background/Aim: Vitamin A (all-trans-retinol, ATRol) serves as a precursor for all-trans-retinoic acid (ATRA), a ligand for the retinoic acid receptor (RAR), representing a potent regulator for many physiological processes. While murine melanoma cells are highly sensitive to retinoid treatment, human melanoma cells have developed still unidentified mechanisms that mediate cellular retinoid resistance. One of the key retinoid metabolizing enzymes is lecithin retinol acyltransferase (LRAT), which catalyzes the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Other genes such as CYP3A4, CYP2C9, ADH4, ADH1A, and CYP1A2 enriched in the cytochrome P450 pathway are observed as metabolically active procarcinogens to genotoxic intermediates, and an association has been found between CYP enzyme activity and the risk to develop several forms of cancer. Amann et al (2015) found that the retinoic acid receptor (RAR) regulated enzyme CYP26a1 showed a significantly lower expression in the lecithin retinol acyltransferase (LRAT)-overexpressing murine melanoma B16F10 cell line. The absence of LRAT-catalyzed retinol esterification is important for mediating retinoid sensitivity in murine melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes such as CYP3A4, CYP2C9, ADH4, ADH1A, and CYP1A2 enriched in the cytochrome P450 pathway are observed as metabolically active procarcinogens to genotoxic intermediates, and an association has been found between CYP enzyme activity and the risk to develop several forms of cancer. Amann et al (2015) found that the retinoic acid receptor (RAR) regulated enzyme CYP26a1 showed a significantly lower expression in the lecithin retinol acyltransferase (LRAT)-overexpressing murine melanoma B16F10 cell line. The absence of LRAT-catalyzed retinol esterification is important for mediating retinoid sensitivity in murine melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this synergistic interaction between E7 and E 2 resulted in distinct gene expression profiles even within the same ontological processes compared with that in the groups that did not develop cancer (FVB, FVB+E 2 and K14E7). Although some of these genes have already been implicated in cancer, a number are new in the context of CC; for example, Nppc is expressed in prostate cancer ( 37 39 ), GDPD3 is overexpressed in luminal B type breast cancer ( 40 ), MGAT4C is associated with prostate cancer risk ( 41 ), IL1R2 is observed in relation to colon cancer and is associated with enhanced angiogenesis ( 42 ), and LRAT is involved in the metabolism of retinoic acid, which when overexpressed, increases the sensitivity of cells to carcinogens ( 43 ). Most notably, the synergistic effect of the HPV16-E7 oncoprotein and E 2 on the downregulation of the Granzyme gene family was observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For some NR, there may be benefit from the reciprocal approach of small molecule facilitation of NR A/B activity. Retinoids in various forms are key to chemotherapy for various dermatologic and non-dermatologic benign hyperproliferative and malignant neoplastic pathologies [133,134]. However, their use is often limited by metabolic inactivation or dose toxicity.…”
Section: Conclusion and Implications From Considering A/b Region Intmentioning
confidence: 99%